G332.5-5.6, a new Galactic supernova remnant - Reynoso, E.M. (2007)
We present radio observations of the source G332.5-5.6, a candidate supernova remnant (SNR). Observations have been performed with the Australia Telescope Compact Array (ATCA) at two frequencies, 1.4 and 2.4 GHz. Our results confirm that G332.5-5.6 is an SNR, with a spectral index α = -0.7 ± 0.2 for the whole source and an average fractional polarization of ∼35 per cent at 2.4 GHz. The central component is coincident with extended X-ray emission, and the distance to the SNR is estimated to be ∼3.4 kpc. Based on its radio and X-ray morphology, this SNR should be classified as a composite, and we suggest that it belongs to a trident-shaped subclass like G291.0-0.1. © 2006 RAS.